Images of Muhammad narratives of the prophet in Islam across the centuries - Khalidi, Tarif 1938- (Doubleday, 2009)
In IMAGES OF MUHAMMAD, Tarif Khalidi examines the ways Muhammad has been depicted and revered from the immediate aftermath of his death to the present day. With scholarly authority, Khalidi explores how the biography of Muhammad has been constructed, reconstructed, and utilized in various Islamic cultures, and traces the influences that have shaped his image, including the profound effect of negative perceptions promulgated by the West. As he describes the great variety of Islamic beliefs and practices, Khalidi illuminates the values and ideas shared by the Sunni, Shia, and Sufi sects, as well as the differences among them, providing Western readers with a clear, objective perspective on the current conflicts within the Muslim world as well as their global repercussions